Final environmental statement : proposed 1977 Outer Continental Shelf oil and gas lease sale offshore the North Atlantic States : OCS sale no. 42 - United States. Bureau of Land Management. ([Washington] : The Bureau, 1977)
At head of title: United States Department of the Interior. Bibliography: v. 3, p. 1624-1683. Mode of access: Internet. 17